IFN-γ is required for cytotoxic T cell-dependent cancer genome immunoediting - Kazuyoshi Takeda (Nature Portfolio, 2017)
T cell mediated anti-tumour immune responses result in the emergence of an immune-resistant population in a process called immunoediting. Here, the authors show that immunoediting is associated with an increase in genomic rearrangements of tumour cells that requires both cytotoxic T cells and IFNγ exposure.